Abdominal Contouring and Male Gender: Analysis of Complications Using the National Quality Improvement Program Database. Issue 4 (October 2019) - Donato, Daniel P.; Simpson, Andrew M.; Garlick, Jared W.; Kwok, Alvin C.; Crombie, Courtney; Agarwal, Jayant P.
Abstract : Background: Males represent a significant portion of patients undergoing abdominal contouring. Despite this, there are few studies examining the implication of gender on complications. Objective: The aim of this study was to examine the association between gender and early postoperative outcomes in patients undergoing abdominal contouring procedures. Methods: The American College of Surgeons National Surgical Quality Improvement Program database (2006–2016) was queried to identify subjects undergoing panniculectomy or abdominoplasty. Minor and major complications were identified. Operative time and length of hospital stay were evaluated. A logistic regression model was used to examine associations between patient gender and adverse outcomes. Results: Ten thousand four hundred seventy-three patients were identified. Of these, 4369 underwent abdominoplasties, and 6104 underwent panniculectomies. Males represented a higher percentage of the panniculectomy cohort (15.3% vs 9.2%). Males were older and generally had more comorbidities including diabetes, hypertension, chronic obstructive pulmonary disease, and elevated body mass index. Males also had a higher American Society of Anesthesiologists classification ( P < 0.001). In the abdominoplasty cohort, male gender is an independent risk factor for any complication (odds ratio [OR], 1.3; confidence interval [CI], 1.16–1.45; P < 0.001) and major complications (OR, 1.52; CI, 1.01–2.29; P = 0.043). In the panniculectomy cohort, male gender is also an independent risk factor for any complication (OR, 1.47; CI, 1.24–1.75; P < 0.001) and major complications (OR, 1.43; CI, 1.12–1.83; P < 0.001). Males also had a significantly longer operative times in this cohort (171.3 vs 157.5 minutes; P < 0.001). Conclusions: Male gender is independently associated with minor and major complications in these patient populations. With this knowledge, plastic surgeons may be better able to identify higher-risk individuals and educate patients on their risk profile.